Plasma and platelet catecholamine and catecholamine sulfate response to various exercise tests - Strobel, Günther; Friedmann-Bette, Birgit; Jost, Joachim; Bärtsch, Peter (American journal of physiology. Endocrinology and metabolism, 1994)
We tested the hypothesis that platelet and plasma catecholamine sulfates (CA-S) and platelet catecholamines (CA) reflect the overall sympathoadrenergic activation by exercise of 1 h duration. Ten well-trained subjects performed a low-intensity [62% maximum O2 consumption (VO2max); LI] and a high-intensity exercise test (77% VO2max; HI) and two tests at a similar average power output that consisted of 20 min at 77% VO2max and 40 min at 62% VO2max (HI/LI) and vice versa (LI/HI). Plasma norepinephrine sulfate (NE-S) increased to higher levels after HI than after LI exercise (15.5 +/- 2.1 vs. 8.9 +/- 0.7 nmol/l). Immediately after HI/LI and LI/HI plasma NE-S was similarly increased (9.59 +/- 1.1 vs. 9.96 +/- 1.3 nmol/l), whereas norepinephrine was higher after LI/HI than after HI/LI (23.0 +/- 3.2 vs. 15.7 +/- 2.3 nmol/l). Platelet CA and CA-S were increased only after HI. In conclusion, the plasma NE-S response to exercise parallels the overall sympathetic activation. These results support the hypothesis that plasma NE-S measured immediately after exercise reflects the overall sympathoadrenergic activity over prolonged periods of exercise. Platelet CA and CA-S poorly reflect sympathoadrenergic activation.
Falsche Namensform in der Verantwortlichkeitsangabe, richtig: Bärtsch, Peter
Gesehen am 17.01.2024